Cephalic Indices of Some Birds in Relation to Their Feeding Habits - Kushwaha, Pramod Kumar (Academic Voices: A Multidisciplinary Journal, 2011)
The shape and size of skull and arrangement of mouth parts play an important role to determine the food and feeding behaviour of birds. The cephalic or head index is a ratio between breadth and length of head. The numerical procedure of cephalic indices of birds represent an important taxonomic character and also help to establish the relationship of feeding habits to visual and acoustic organs of birds. Birds have evolved a great variety of beaks according to their food habits. Due to different food habits found in birds, they possess various types of beaks of special structure. This article deals with cephalic indices of some birds of Uttar Pardesh (India) in relation to their feeding habits. Keywords Skull, bill, measurement, ratio, relation DOI: http://dx.doi.org/10.3126/av.v1i0.5311 Academic Voices 2011; 1: 49-55